Effect of Ultraviolet-C Radiation on the Morphology of Cyanobacteria Nostoc sp. LBALBR-2 Isolated from Supply Reservoir (Belém, Pará, Brazil) (Research, Society and Development, 2022)
Cyanobacteria are photosynthetic prokaryotic organisms that in aquatic environments can compose the phytoplankton and phytobenthos, being important in the primary  production of these ecosystems. The objective of this work was to identify the main morphological variations of the cells, filaments and thallus of the cyanobacteria Nostoc sp. LBALBR-2 submitted to ultraviolet radiation (UV-C) in microcosm systems. The cyanobacteria Nostoc sp. was subjected to four treatments: 1- control treatment in nutrient medium; 2- treatment in nutrient medium with exposure to UV-C radiation; 3- control treatment in medium without nutrients and 4- treatment in medium without nutrients with exposure to UV-C radiation. Optical density and chlorophyll-a analyses were performed to determine the growth of Nostoc populations and microscopic analyses to characterize the morphological development of the species. Lack of nutrients generated short trichomes with terminal heterocytes, scattered solitary akinetes and appearance of hormogonia. On nutrient medium the trichomes of Nostoc sp. showed predominantly the vegetative serial form. Cultures exposed to UV-C produced anomalous cells, thick mucilage, fragmented trichomes and hormogonia. It is concluded that Nostoc sp. LBALBR-2 grew well under eutrophication conditions and although it showed cell deformation it was resistant to UV-C radiation.